2019
DOI: 10.1093/cid/ciz704
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Infancy Outcomes for Microcephaly and/or Small for Gestational Age Zika-Exposed Infants

Abstract: Background Zika-exposed infants with microcephaly (proportional or disproportional) and those who are small for gestational age without microcephaly should be closely followed, particularly their growth trajectories. They are at high risk of adverse outcomes in the first year of life. Antenatal Zika virus (ZIKV) exposure may lead to adverse infant outcomes including microcephaly and being small for gestational age (SGA). ZIKV-exposed infants with a diagnosis of microcephaly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Nonetheless, our diagnostic system has proven to be sufficient for screening of infectious individuals as previous findings suggest minimal infectivity in patients with high Ct values and their low likelihood of viral transmission. 22 , 23 Moreover, the viral count is indicative of disease severity and infectivity of the infected individuals. Our system’s ability to report a quantitative value correlated with the viral load offers critical quantitative information that cannot be obtained from current readout methods, such as visual inspection or lateral flow strips.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, our diagnostic system has proven to be sufficient for screening of infectious individuals as previous findings suggest minimal infectivity in patients with high Ct values and their low likelihood of viral transmission. 22 , 23 Moreover, the viral count is indicative of disease severity and infectivity of the infected individuals. Our system’s ability to report a quantitative value correlated with the viral load offers critical quantitative information that cannot be obtained from current readout methods, such as visual inspection or lateral flow strips.…”
Section: Resultsmentioning
confidence: 99%
“…ZIKV-specific IgM has been detected in the CSF of neonates with fetal microcephaly, which is indicative of central nervous system (CNS) infection, and suggests that infection of the developing fetus may be required for fetal microcephaly to develop, not just infection of the mother [49]. Fetal microcephaly and other negative fetal outcomes are most closely linked with maternal ZIKV infection early in pregnancy (first trimester), with one study finding that the risk of below-average neurodevelopment fell by 46% each trimester (Figure 1) [16,50,51,52,53]. In a case-control study of factors associated with the development of CZS, no link was found with maternal age, previous dengue virus infection, or exposure to alcohol, drugs, or tobacco [50].…”
Section: Pathogenesis During Pregnancy Infancy and Childhoodmentioning
confidence: 99%
“…However, a separate study observed that women who gave birth to microcephalic infants had significantly higher serum neutralizing activity and antibodies reactive to the ZIKV envelope protein domain III, compared to control women [54]. Other birth defects linked to ZIKV infection include patent foramen ovale (failure of a natural hole between the left and right atria of the heart to close before birth), clubfoot, cryptorchidism (failure of the testes to descend into the scrotum), ophthalmologic problems, hearing abnormalities, and difficulty swallowing [16,50,51,52]. In some cases, fetal death following maternal ZIKV infection has also been reported [33,53].…”
Section: Pathogenesis During Pregnancy Infancy and Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Although microcephaly is the most evident alteration of CZS, other anomalies resulting from congenital ZIKV infection have been described, even in the absence of this clinical sign [20]. This wide spectrum of clinical manifestations of microcephaly/CZS and its harmful consequences on the child's health and development, certainly increase vulnerability to childhood morbidity and mortality and may produce direct or indirect effects on their survival and development.…”
Section: Introductionmentioning
confidence: 99%